Study of Sun Protection Factor (SPF) Batik Textile Fabric on Solar Radiation in Pekalongan - Liana, Yeni Rima; Baiti, Upik Nur; Fianti, Fianti (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2021)
AbstractThe amount of sunscreen ability is determined through the value of a person's Sun Protection Factor (SPF) when under the sun without experiencing sunburn. This study aims to measure the intensity of sunlight received by batik textile fabrics and SPF measurements to determine the ability of these fabrics to protect sunlight radiation. The research was conducted at the Sorogenen area in Pekalongan City. Intensity data collection is done during sunny weather with temperatures of 300C - 320C from 10.00 to 14.00 WIB. The SPF value can be calculated by comparing the intensity of sunlight without a protective batik cloth with the intensity of sunlight with a protective cloth. The intensity of the average in the range of 10:00 to 14:00 WIB is 85.160 lux to 113.400 lux. The results obtained by fabric with a thickness of 2 mm have a SPF greater than fabric with a thickness of 1 mm. Cotton fabric has the ability to protect against sunlight better than satin and mori cloth. The largest SPF value is owned by a blue cotton cloth with a thickness of 2 mm of 36,06. While the smallest SPF value is owned by yellow cloth with a thickness of 1 mm of 5,24.